Including the public in pandemic planning: a deliberative approach - Braunack-Mayer, Annette J (BioMed Central, 2010)
BACKGROUND: Against a background of pandemic threat posed by SARS and avian H5N1 influenza, this study used deliberative forums to elucidate informed community perspectives on aspects of pandemic planning. METHODS: Two deliberative forums were carried out with members of the South Australian community. The forums were supported by a qualitative study with adults and youths, systematic reviews of the literature and the involvement of an extended group of academic experts and policy makers. The forum discussions were recorded with simultaneous transcription and analysed thematically. RESULTS: Participants allocated scarce resources of antiviral drugs and pandemic vaccine based on a desire to preserve society function in a time of crisis. Participants were divided on the acceptability of social distancing and quarantine measures. However, should such measures be adopted, they thought that reasonable financial, household and psychological support was essential. In addition, provided such support was present, the participants, in general, were willing to impose strict sanctions on those who violated quarantine and social distancing measures. CONCLUSIONS: The recommendations from the forums suggest that the implementation of pandemic plans in a severe pandemic will be challenging, but not impossible. Implementation may be more successful if the public is engaged in pandemic planning before a pandemic, effective communication of key points is practiced before and during a pandemic and if judicious use is made of supportive measures to assist those in quarantine or affected by social isolation measures.